Incentivizing behaviour change to improve diabetes care. Issue 12 (1st May 2013) - Petry, N. M.; Cengiz, E.; Wagner, J. A.; Hood, K. K.; Carria, L.; Tamborlane, W. V.
Abstract : Behavioural economics refers to the study of psychological and cognitive factors that relate to decision‐making processes. This field is being applied increasingly to health care settings, in which patients receive tangible reinforcers or incentives for meeting objective behavioural criteria consistent with healthy lifestyles. This article reviews the background and efficacy of reinforcement interventions in general, and then as applied to behaviours related to diabetes prevention and management. Specifically, reinforcement interventions have been applied with some notable success towards promoting greater attendance at medical appointments, enhancing weight loss efforts, augmenting exercising regimes, improving medication adherence and increasing blood glucose monitoring. Suggestions for promising areas of future research are provided, keeping in mind the controversial nature of these interventions.